Optimization Strategy of Service Marketing Mix in the Development of MICE Services at Wisma Universitas Terbuka - Muhammad Ozi Setiawan; Yulita Suryantari; Linarko Linarko (Utan Kayu Publishing, 2025)
This study aims to analyze the implementation of marketing mix strategies in the development of MICE (Meetings, Incentives, Conferences, and Exhibitions) services at Wisma Universitas Terbuka. The research employed a qualitative method with a descriptive qualitative approach. Data were collected through in-depth interviews, direct observation, and documentation. The findings show that several elements of the 7Ps—such as product, place, price, and physical evidence—have been implemented quite well in supporting MICE services. However, significant weaknesses were identified in the aspects of promotion, process, and human resources. These weaknesses include the absence of a digital promotion strategy, the lack of standardized service procedures, and insufficiently professional competencies among the human resources in the MICE field. This study recommends a strategic integration of marketing mix elements to strengthen brand image and service quality, with particular emphasis on digital transformation and the development of professional human resources. The results are expected to serve as a foundation for formulating marketing strategies that are both applicable and adaptive to the dynamics of the competitive MICE industry, thereby reinforcing Wisma Universitas Terbuka’s position as a leading and reliable institutional MICE service provider.